An Evaluation of Size Effect in CTOD-SENB Fracture Toughness Tests. (2015) - Palombo, Marco; Sandon, Stefano; De Marco, Marco
Abstract: This paper describes the attempt to define a correlation criterion between fracture toughness, expressed in terms of J-integral, J, and crack tip opening displacement, CTOD, and referred to the thickness (B) of a specimen. From a thick component (e.g. B ≥ 150 mm) it is often difficult to take full-size specimens, because of their dimensions, and weight make handling and hence CTOD-testing difficult too; moreover, taking a full size specimens could be not possible because of the shape of the component. Therefore the need to find a correlation criterion between fracture toughness and thickness becomes relevant. A number of CTOD-tests were performed in accordance with BS 7448 part 1 on carbon steel single edge notch bend (SENB) specimens of different size. Through the experimental data a correlation was found that allows to evaluate J and CTOD for specimens with different thickness (higher or lower) than the one characterising tested specimens. The toughness-thickness correlation was verified applying the Weibull statistical weakest link theory adopted by the ASTM standard E1921-13. Furthermore, with the aim to use toughness temperature dependence for adapting testing conditions in reduced thickness specimens, data for specimens tested at different temperatures were compared.